MAIN DIRECTIONS OF CREATING NEW JOBS IN THE SERVICE SECTOR - Abdusaidov, Akmal Abduvaliyevich (THE INNOVATION ECONOMY, 2026)
This article provides a scientific analysis of the main directions of creating new jobs in the service sector in Uzbekistan, modern trends in labor market transformation, and economic, institutional, and digital factors contributing to the expansion of employment in the service segment. The study examines structural changes in the service sector, the role of small business and entrepreneurship, the expansion of remote work forms, diversification of services, and the impact of government programs on employment. The results show that the drivers of creating new jobs in the service sector are directly related to digital technologies, urbanization processes, growth in real incomes, and institutional reforms.